H2O2 sensing through electrochemically deposited thionine coated ITO thin film - Singh, P.; Srivastava, S.; Singh, S. K. (Cellular and Molecular Biology, 2017)
Progression and initiation of different diseases including pulmonary diseases, alzheimer's and tumors are linked with the oxidative stress, an important cause of cell damage. Different antioxidant enzymes are involved in detoxifying reactive oxygen species including hydrogen peroxide (H2O2) that is generated in response to various stimuli and has important role in cell activation & bio-signaling processes. Herein, we developed hydrogen peroxide electrochemical sensor based on horseradish peroxidase (HRP) entrapped polymerized thionine (PTH) film. Electrochemical deposition of thionine (dye) on indium tin oxide (ITO) surface was carried out through chornoamperometry followed by cyclic voltammetry. Deposited thionine thin film obtained was checked for its stability at different scan rates. The PTH-modified electrodes showed linear dependence of peak current with scan rate within the range of 20 to 100 mV sâˆ’1. Thionine used as electron transfer mediator between heme site of HRP and electrode. Cyclic voltammetry showed increase in the reduction peak current due to electrocatalytic reduction of H2O2. The sensor detection limit range from 10-1 _ 102 µM and limit of detection was 0.1µM. The proposed sensor has good storage response, cost effective, high sensitivity and wide linear range that could be used for the fabrication of other enzyme based biosensors.